Complications after proton therapy of choroidal melanoma: A case report - Natalia Kuková; Maria Molnarova; Jana Stefanickova (Ukrainian Society of Ophthalmologists, 2023)
Proton beam therapy is a globe preserving treatment method of choroidal melanoma. It is considered to be less harmful for the tissues around the tumour but the complications such as radiation retinopathy and neuropathy occur according to the dosage of irradiation. The visual outcomes after treatment are variable and dependent on the size of tumour. This article presents a case report of a 44-year-old male with choroidal melanoma in the left eye. Patient was examined in our ophthalmology practice because of photopsia and blurry vision during physical activity. After full ophthalmologic examination, fundus photography, optic coherent tomography, fluoresceine angiography and ultrasonography the diagnosis of malignant melanoma of choroid was set. The patient was referred to a proton center to undergo a proton therapy of choroidal melanoma in the left eye. Follow-up treatment of severe postradiation retinopathy and neuropathy is presented in the article. The patient took intravitreal bevacizumab injections and the panretinal lasercoagulation was performed. After one and half year follow up the melanoma is stable after therapy with no metastases.